Effect of raw and fermented pomegranate pomace on performance, antioxidant activity, intestinal microbiota and morphology in broiler chickens. Issue 2 (4th March 2021) - Gungor, Emrah; Altop, Aydin; Erener, Guray; Coskun, Isa
ABSTRACT: The present study was conducted to investigate the effects of raw (PP) and fermented pomegranate pomace (FP) on performance, antioxidant activity, caecal microbiota and ileal morphology in broiler chickens. A total of 175 male broiler chicks were allocated to five treatment groups with five replicates and seven birds per replicate in a completely randomised design. Dietary treatments included a soy-corn based diet (control), diets supplemented with PP at 5 (5PP) and 10 g/kg (10PP), and diets supplemented with FP at 5 (5FP) and 10 g/kg (10FP). Dietary PP and FP did not change the body weight and feed conversion ratio. Moreover, dietary PP and FP did not alter the serum glutathione peroxidase, superoxide dismutase, and catalase levels but decreased malondialdehyde ( p < 0.05) in breast meat. Caecal Clostridium perfringens count was decreased in broiler chickens of groups 10PP, 5FP and 10FP ( p < 0.05). However, PP and FP had detrimental effects on the ileum morphology of broiler chicks. The villus height was decreased in the 10PP, 5FP and 10FP groups compared with the control group ( p < 0.01). Crypt depth was higher in the 5PP and 10FP groups than control and 10PP groups ( p < 0.01). The villus height to crypt depth ratio was also decreased in 5PP, 5FP, and 10FP groups ( p < 0.01). These results suggest that PP and FP have the potential to be used in broiler diets as antioxidant and antimicrobial agents. However, detailed studies should be conducted to investigate the underlying reasons for the detrimental effects on ileal morphology.